Differential effect of regadenoson versus dipyridamole on heart rate in patients with left bundle branch block: How does it affect the results of pharmacological nuclear stress testing?. (February 2019) - Assaad, Mahmoud; Berry, Abeer; Palanisamy, Jaishree; Fenner, Joseph; Zughaib, Marcel
Background: Myocardial perfusion imaging (MPI) stress test is performed either using exercise as a stress modality or through the use of pharmacological vasodilator agents in those who cannot exercise. Regadenoson and dipyridamole are some of the most common vasodilator agents used. We aim to study the effect of these agents on the heart rate and the imaging results. Methods: This was a retrospective study which included 187 patients with left bundle branch block. Patients received either dipyridamole or regadenoson during the myocardial perfusion imaging stress test. Charts were reviewed, and patient characteristics were recorded, as well as baseline heart rate, peak heart rate during stress, and angiographic data if available. Results: Regadenoson increased peak, absolute and relative heart rates significantly more compared to dipyridamole. The peak heart rate for Regadenoson was 94.1 ± 17.36 and for dipyridamole it was 85.38 ± 16.48 BPM (P < 0.001). The relative and absolute heart rate increase in the regadenoson group were 40.75 ± 23.01% and 26.06 ± 13.44 BPM, respectively. The relative and absolute heart rate increase in the dipyridamole group were 24.61 ± 18.25% and 16.23 ± 10.97 BPM. The frequency of reversible septal defects was similar in both groups (54% for Regadenoson vs. 63% for Dipyridamole; P = 0.24). Conclusions: There is a statistically significant increase in heart rate with the use of regadenoson for MPI compared to dipyridamole. However, the number of septal perfusion defects was similar between the two groups. The effect of this increase in heart rate, while statistically significant, is likely of no clinical significance.